A Strategy to Improve Pass Rates of Written Postgraduate Statistics Modules - Sesale, Eunice Lebogang; Ramarumo, Tshepo; Seeletse, Solly Matshonisa (Universitas Sarjanawiyata Tamansiswa, 2023)
Many universities apply student support services to undergraduate (UG) students, but some postgraduate (PG) cases need it. South African universities have intensified PG admissions. PG students admitted with a minimum admission mark are not PG-ready. For the Bachelor of Science Honours (BSc Honours) in Statistics (Stats) that requires intense Math conceptual knowledge to apply to Stats concepts, where competition is high, only top students can be competitive. In South Africa, the job market prioritizes graduates from historically white higher education institutions (HEIs), and formerly black and newer university graduates’ struggle. Non-stop students from the latter universities are not easily employed, so they need a stimulus. This study focuses on BSc Honours (Stats) students who perform low for intervention to improve their performance. Measures were proposed for student conduct and behavior to enable lecturers to constantly stimulate the teaching and monitor and evaluate progress while continuously assessing the students. The study followed an experimental design. Students were ordered to practice with module exercises using statistical software packages in the computer laboratory. Exceedingly high pass rates of 100% were realized. The methods were viewed as effective and beneficial.